Clinical and Radiographic Features of Nevoid Basal Cell Carcinoma Syndrome: A Case Report - Babu, G Subhas; Pillai, Devika S; Hegde, Shruthi; Hegde, Padmaraj; Ajila, Vidya (UI Scholars Hub, 2022)
Nevoid Basal Cell Carcinoma Syndrome, also called as Gorlin Gotz syndrome is an autosomal dominant disorder characterized by the presence of multiple odontogenic keratocysts (OKCs) of the jaw, basal cell carcinomas and skeletal anomalies. Presence of multiple OKCs is the first clinical manifestation in majority of the cases. Early diagnosis and treatment are of utmost importance in reducing the severity of this syndrome. We hereby report a rare case of Gorlin Goltz syndrome in a 28 years old female patient who presented with multiple cystic lesions in the jaws. Present case also highlights the clinical, radiographic and histopathologic features of this uncommon syndrome.